The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1161/01.res.0000259045.49371.9c
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Extracellular Signal-Regulated Kinase 5 Reduces Cardiac Apoptosis and Dysfunction via Inhibition of a Phosphodiesterase 3A/Inducible cAMP Early Repressor Feedback Loop

Abstract: Substantial evidence suggests that the progressive loss of cardiomyocytes caused by apoptosis significantly contributes to the development of heart failure. beta-Adrenergic receptor activation and subsequent persistent phosphodiesterase 3A (PDE3A) downregulation and concomitant inducible cAMP early repressor (ICER) upregulation (PDE3A/ICER feedback loop) has been proposed to play a key role in the pathogenesis of cardiomyocyte apoptosis. In contrast, insulin-like growth factor-1 can activate cell survival path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 43 publications
0
60
0
1
Order By: Relevance
“…141 In addition, the same group demonstrated a link between ERK5 activity induced by insulin-like growth factor-1 and phosphodiesterase 3A/inducible cAMP early repressor loop to regulate myocyte apoptosis and contractile function. 142 The reason for such discrepancies is not clear, although different MEK5 isoforms used in these studies may be one of the causes. Potentially, intracellular targeting of ERK5 activity to different compartments may dictate specific functional outcome.…”
Section: Erk5 In Eccentric Hypertrophy and Death Regulation In The Heartmentioning
confidence: 93%
See 1 more Smart Citation
“…141 In addition, the same group demonstrated a link between ERK5 activity induced by insulin-like growth factor-1 and phosphodiesterase 3A/inducible cAMP early repressor loop to regulate myocyte apoptosis and contractile function. 142 The reason for such discrepancies is not clear, although different MEK5 isoforms used in these studies may be one of the causes. Potentially, intracellular targeting of ERK5 activity to different compartments may dictate specific functional outcome.…”
Section: Erk5 In Eccentric Hypertrophy and Death Regulation In The Heartmentioning
confidence: 93%
“…Ras-Raf-MEK-ERK Nanoon and Nanoon-like syndromes [27][28][29][30][31][32][33][34][35][36][37][38] Concentric hypertrophy1 54,55 ( [134][135][136] Eccentric hypertrophy12 [137][138][139]141 Cardiac protection1 142 Contractile dysfunction2 142 …”
Section: Developmental and Pathophysiological Roles Of Map Kinases Inmentioning
confidence: 99%
“…8 H 2 O 2 and advanced glycation end products (AGE), 2 well-known mediators of diabetes, negatively regulated ERK5 transcriptional activity via ERK5-SUMOylation in endothelial cells. Because ERK5 demonstrates a cardio-protective effect, 7 we investigated the effect of STZ-mediated hyperglycemia and MI on the ERK5-SUMOylation. As shown in Figure 2, we found a slight increase of ERK5-SUMOylation in both the DM (with sham operation) and MI (without STZ treatment) groups.…”
Section: Erk5-sumoylation In Dm؉mi Modelmentioning
confidence: 99%
“…ERK5, an atypical mitogen activated protein kinase with transcriptional activity, negatively regulates the executor PDE3A-ICER feedback loop and subsequent apoptosis. 7 Our recent data indicated that ERK5 transcriptional activity itself is subjected to downregulation by reactive oxygen species (ROS) and advanced glycogen endproducts (AGE)-dependent small ubiquitin-related modification (SUMO), and inhibits KLF2 and eNOS expression in endothelial cells. 8 ERK5-SUMOylation at the NH 2 -terminal region (K6 and K22) significantly inhibits COOH-terminal ERK5 transcriptional activity.…”
mentioning
confidence: 99%
“…6 The inducible cyclic AMP (cAMP) early repressor has been demonstrated to influence cell growth in neuroendocrine tissue, cardiac myocytes and the liver. [7][8][9] Recently, it has been proposed as a tumor suppressor gene in prostate and pituitary cancers. 10,11 We previously documented that ICER was downregulated at diagnosis of acute leukemia in a cohort of pediatric patients, whereas CREB protein was found to be overexpressed.…”
Section: Introductionmentioning
confidence: 99%